Scattering from a Buried PEMC Cylinder due to a Line Source Excitation above a Planar Interface Between Two Isorefractive Half Spaces - Hamid, A. K.; Cooray, F. (Advanced Electromagnetics, 2019)
A solution to the problem of scattering from a perfect electromagnetic conducting (PEMC) circular cylinder buried inside a half-space and excited by an infinite electric line source is provided. The line source is parallel to the cylinder axis, and is located in the other half-space. The two half spaces are isorefractive to each other. The source fields when incident at the planar interface separating the two half spaces, generate fields that are transmitted into the half-space where the cylinder is. These fields then become the known basic incident fields for the buried PEMC cylinder. Scattering of these incidents fields by the cylinder will consequently generate fields at the interface that get reflected back into the same half-space and transmitted frontward into the source half-space, all of which are unknown. Imposing appropriate boundary conditions at the surface of the buried cylinder and at a specified point on the interface, enables the evaluation of these unknown fields. The refection coefficient at the specified point is then computed for cylinders of different sizes, to demonstrate how it varies with the PEMC admittance of the buried cylinder, the intrinsic impedance ratio of the two isorefractive half-spaces, and the burial depth of the cylinder.